Landasan Proyeksi Pemberitaan Pertanian Kabupaten Jember di Masa Depan: Analisis Linguistik Korpus pada Media Lokal dan Nasional - Anita Widjajanti; Yoga Yolanda; Rusdhianti Wuryaningrum (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Online news media is the main source of information for the public regarding agricultural news in Jember Regency, while each media outlets has its own requirements in reporting such news. The purpose of this study is to reveal the similarities and differences between local and national news topics in reporting agriculture in Jember Regency. The data used is language corpus data in news articles from four local media outlets and four national media outlets. The corpus data was processed using Orange Data Mining. Various widget features were utilized, with the main widgets related to this study being Word Cloud & Topic Modelling. The results of the data processing were then analyzed using the Tagset Ucrel Semantic Analysis System (Tagset USAS) reference. Through the analysis results, significant similarities and differences were found between local and national media in reporting on agriculture in Jember Regency. The similarities found are that both types of media use relatively similar news objects and subjects, which are in 9 semantic categories. The differences found were that local media emphasized the role of the local government, while national media emphasized agricultural production and processing. These results illustrate the differing media needs regarding issues that must be addressed, both at the local and national levels. The findings of this study are beneficial for news media in determining the focus of agricultural reporting in Jember Regency in the future, by considering the relevance over personal interests.